Concurrent Anticonvulsant/Ketogenic Diet Efficacy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2009)
Researchers at the Johns Hopkins Hospital, Baltimore, studied retrospectively the comparative efficacy of six most frequently used anticonvulsants when employed in combination with the ketogenic diet (KD) for treatment of 115 children with epilepsy.